A Novel PDE4D Inhibitor BPN14770 Reverses Scopolamine-Induced Cognitive Deficits via cAMP/SIRT1/Akt/Bcl-2 Pathway - Wang, Yulu; Gao, Shichao; Zheng, Victor; Chen, Ling; Ma, Min; Shen, Shichen; Qu, Jun; Zhang, Hanting; Gurney, Mark E.; O’Donnell, James M.; Xu, Ying (Frontiers in Cell and Developmental Biology, 2020)
A global, quantitative proteomics/systems-biology analysis of the selective pharmacological inhibition of phosphodiesterase-4D (PDE4D) revealed the differential regulation of pathways associated with neuroplasticity in memory-associated brain regions. Subtype selective inhibitors of PDE4D bind in an allosteric site that differs between mice and humans in a single amino acid (tyrosine versus phenylalanine, respectively). Therefore to study selective inhibition of PDE4D by BPN14770, a subtype selective allosteric inhibitor of PDE4D, we utilized a line of mice in which the PDE4D gene had been humanized by mutating the critical tyrosine to phenylalanine. Relatively low doses of BPN14770 were effective at reversing scopolamine-induced memory and cognitive deficits in humanized PDE4D mice. Inhibition of PDE4D alters the expression of PKA, Sirt1, Akt, and Bcl-2/Bax which are components of signaling pathways for regulating endocrine response, stress resistance, neuronal autophagy and apoptosis. Treatment with a series of antagonists, such as H89, sirtinol, and MK-2206, reversed the effect of BPN14770 as shown by behavioral tests and immunoblot analysis. These findings suggest that inhibition of PDE4D enhances signaling through the cAMP-PKA-SIRT1-Akt -Bcl-2/Bax pathway and thereby may provide therapeutic benefit in neurocognitive disorders.